Electrocatalytic hydrogenation and oxidation of glucose and xylose on mesoporous carbon-supported Au nanocatalysts. (1st January 2023) - Oña, Jay Pee; Latonen, Rose-Marie; Kumar, Narendra; Peurla, Markus; Angervo, Ilari; Grénman, Henrik
Highlights: Higher activity of smaller gold nanoparticles (AuNPs) towards glucose and xylose hydrogenation and oxidation was observed. Higher extent of HER observed with xylose solution compared to glucose when moving towards more negative potentials ( in-situ FTIR-ATR). Abstract: Electrocatalytic conversion of hemicellulose-derived glucose and xylose presents a sustainable approach to utilize renewable energy (e.g. solar, wind) to produce value-added chemicals. In this work, the electrochemical hydrogenation and oxidation of glucose and xylose at ambient conditions were studied using dispersed, mesoporous Sibunit Carbon (SC)-supported Au nanocatalysts (SC/AuNPs) with different cluster sizes (4.4 nm, 5.9 nm, 10-30 nm), providing novel results on the cluster size - activity relation. For the electrocatalytic hydrogenation (ECH) of glucose and xylose into sorbitol and xylitol, respectively, higher conversion rates were obtained when more negative potentials were applied. This indicates that the hydrogenation reaction proceeds concurrently with hydrogen evolution reaction (HER). SC/AuNPs with smaller Au clusters were more active towards glucose or xylose ECH at all potentials applied. The selectivity (Faradaic efficiency) increased towards more negative potentials for glucose ECH but followed an opposite trend for xylose ECH. Analysis using in-situ FTIR-ATR spectroscopy showed that water adsorption which leads to HER, was more extensive in xylose solution than in glucose solution at lower potentials. This would indicate greater inhibition of xylose ECH than glucose ECH at more negative potentials. The electrocatalytic oxidation (ECO) of glucose and xylose to gluconic acid and xylonic acid, respectively, was observed to occur at -0.05, +0.3, and +0.4 V (vs Ag/AgCl) using the present electrocatalytic set up. Constant-potential electrolysis at these potentials showed differences in ECO rate depending on the applied potential and average Au cluster size. The highest glucose and xylose ECO rate was obtained for the SC/AuNPs with the smallest average Au cluster size (4.4 nm) at +0.3 V. Constant-potential electrolysis of the sugars at +0.3 V using this catalyst resulted in 42 % yield of gluconic acid and 32 % yield of xylonic acid in 6 hours, both with a very low Au loading of 0.08 % wt.. These results show the strong influence of Au cluster size on the catalytic activities of SC/AuNPs toward sugar ECH or ECO. Graphical abstract: Image, graphical abstract